2014
DOI: 10.1007/7651_2014_179
|View full text |Cite
|
Sign up to set email alerts
|

A Doxycycline-Inducible System for Genetic Correction of iPSC Disease Models

Abstract: Patient-derived induced pluripotent stem cells (iPSCs) are valuable tools for the study of developmental biology and disease modeling. In both applications, genetic correction of patient iPSCs is a powerful method to understand the specific contribution of a gene(s) in development or diseased state(s). Here, we describe a protocol for the targeted integration of a doxycycline-inducible transgene expression system in a safe harbor site in iPSCs. Our gene targeting strategy uses zinc finger nucleases (ZFNs) to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 12 publications
(10 reference statements)
0
22
0
Order By: Relevance
“…Furthermore, deletion of the enhancer occupied by SMAD3 was also associated with a significant reduction in mRNA and protein expression of SOX17, FOXA2 and CXCR4 (Figures 1I, 1J, S1G and S1H), which together identify DE (D’Amour et al, 2005; Green et al, 2011; Loh et al, 2014; Ogawa et al, 2013). Passage-matched hESCs and hESCs containing a green fluorescent protein (GFP) expression system (Sim et al, 2015) were used as controls. We used the CRISPR system to insert the components of the GFP expression system into the AAVS1 loci to create a control that had undergone the same manipulations used to create the SMAD3 enhancer deletions.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, deletion of the enhancer occupied by SMAD3 was also associated with a significant reduction in mRNA and protein expression of SOX17, FOXA2 and CXCR4 (Figures 1I, 1J, S1G and S1H), which together identify DE (D’Amour et al, 2005; Green et al, 2011; Loh et al, 2014; Ogawa et al, 2013). Passage-matched hESCs and hESCs containing a green fluorescent protein (GFP) expression system (Sim et al, 2015) were used as controls. We used the CRISPR system to insert the components of the GFP expression system into the AAVS1 loci to create a control that had undergone the same manipulations used to create the SMAD3 enhancer deletions.…”
Section: Resultsmentioning
confidence: 99%
“…36 Inducible and megakaryocyte transgene expression can also be performed using the PPP1R12C (AAVS1) "safe harbor" locus, which prevents deleterious off-target cloning and gene silencing that can occur during differentiation. [69][70][71][72] Modulation of transcriptional master regulators, such as PU.1, can be used to eliminate unwanted myeloid cell fates 71 that may contribute to the enzymatic injuries of megakaryocytes.…”
Section: Stem Cell Choicementioning
confidence: 99%
“…It was originally recovered as a natural site of integration of wild-type AAV in cultured human cell lines 5 and gained popularity due to, on one hand, its ability to afford robust expression of inserted reporter transgenes in various cell types, including hPSCs (embryonic stem cells and induced pluripotent stem cells (iPSCs)) and, on the other hand, the development of efficient commercially available tools for its targeting. 6,7,8,9 However, more systematic recent studies have revealed that the AAVS1 locus is prone to silencing in some cell lineages. 10 Furthermore, a number of applications require dual transgene or reporter expression or transgene insertion in hPSC lines where the AAVS1 locus is already occupied by other transgenic sequences, for example by an inducible genome editing enzyme.…”
Section: Introductionmentioning
confidence: 99%